Evolution of a salt marsh in the southeastern North Sea region – Anthropogenic and natural forcing. (5th March 2019) - Müller-Navarra, Katharina; Milker, Yvonne; Bunzel, Dorothea; Lindhorst, Sebastian; Friedrich, Jana; Arz, Helge; Schmiedl, Gerhard
Abstract: Salt-marsh sediments of the southeastern North Sea provide an archive to unravel the influences of coastal management and natural processes such as storm-tide deposition on salt-marsh development. We present a record of salt-marsh evolution during the past century from the Bay of Tümlau (northwestern Germany) based on fossil foraminiferal assemblages and sedimentological data. After diking the hinterland of the Bay of Tümlau in 1935 CE and commencing marsh management, the environment at the study site changed from a tidal flat to a salt marsh. Salt-marsh sediment accretion is influenced by recurrent dredging events, as indicated by layers rich in calcareous tidal-flat foraminifera, and redeposition of siliciclastic particles from the surrounding tidal flats during storm tides. The latter fostered the establishment of a typical salt-marsh foraminiferal fauna dominated by the agglutinating species Entzia macrescens . Storm-tide layers have a lighter sediment color and commonly a more negatively skewed grain-size distribution with variable sorting. The observed long-term coarsening of the salt-marsh sediment likely reflects the landward progression of the vertical erosional cliff and the depletion of fine-grained sediment particles in the tidal flats under the influence of sea-level rise. Supra-tidal conditions, resulting from natural protection measures and abandonment of dredging, are indicated by the occurrence of Balticammina pseudomacrescens around 2001 CE. This species is adapted to only occasional submergence during storm tides. The recent increase in elevation is accompanied by establishment of high-marsh vegetation and characterized by a present height of the marsh surface 50 cm above mean high water springs. During the past sixty years, average sediment accretion rates decreased from 18 to 11 mm yr −1 reflecting the maturing of the salt marsh. These rates clearly outpace the recent mean sea-level rise in the southern North Sea demonstrating that the regional salt marshes are still resilient to sea-level rise.